2018
DOI: 10.5267/j.dsl.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

ANN and RSM approach for modelling and multi objective optimization of abrasive water jet machining process

Abstract: Abrasive Water Jet Machining is one of the novel nontraditional cutting processes found diverse applications in machining different kinds of difficult-to-machine materials. Process parameters play an important role in finding the economics of machining process at good quality. This research focused on the predictive models for explaining the functional relationship between input and output parameters of AWJ machining process. No single set of parametric combination of machining variables can suggest the better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…10 As a result, the ANN method was an appealing choice for numerous researchers when modeling and predicting AWJ machining performances of different materials such as Aluminum alloy, 11 rocks, 9 trip steel, 12 Ti-6Al-4V, 13 and granite. 14 Nevertheless, a very limited number of ANN models have been developed for fibrous polymer composites. 15,16…”
Section: Introductionmentioning
confidence: 99%
“…10 As a result, the ANN method was an appealing choice for numerous researchers when modeling and predicting AWJ machining performances of different materials such as Aluminum alloy, 11 rocks, 9 trip steel, 12 Ti-6Al-4V, 13 and granite. 14 Nevertheless, a very limited number of ANN models have been developed for fibrous polymer composites. 15,16…”
Section: Introductionmentioning
confidence: 99%
“…Under such circumstances, the effective utilization of experimental, modeling, and optimization methodology makes possible a greater improvement in decision-making with new technological solution that can simultaneously satisfy and control the several distinctive as well as contradictory objectives (multi-objective) in order to make the HAJM process as an excellent choice for machining of advanced engineering ceramic and quartz materials. Several statistical and computational approaches such as MRA [1][2][3], RSM [4][5][6][7][8][9], ANN [10][11][12][13] have been applied for predictive modeling and Taguchi method [14][15][16][17][18], GRA [19][20][21][22][23][24][25], desirability function approach of RSM [26][27][28][29][30][31][32], PCA [33,34], TOPSIS [35], GA [11,12,36,37], PSO [38,39] have been employed for parametric as well as process optimization in abrasive jet machining with the help of carrier gas or liquid medium. Extensive studies have been reported by employing various experimental designs, modeling techniques, and optimization approaches in order to assess or investigate th...…”
Section: Introductionmentioning
confidence: 99%
“…Srinath Reddy et al (2018) have carried out multi-objective optimization of AWJM process using ANN. Modeling based on RSM approach is capable of predicting optimized responses.…”
Section: Introductionmentioning
confidence: 99%